ANALYSIS OF THE APPLICATION OF TAX AGGRESSIVITY IN EFFORTS OF TAX CHARGE EFFICIENCY (STUDY AT PT. BAGUS SATRIA MANDIRI) - Ahmad Fauzi; Eka Nurmala; Syafrida Hani (SEAN Institute, 2023)
This study aims to analyze the application of tax aggressiveness that should be carried out by PT. Bagus Satria Mandiri as an effort to increase the efficiency of the tax burden for 2019, 2020 and 2021. This research is a descriptive type of exploratory study approach, because it aims to describe conditions or phenomena that occur in the field. The type of data used in this study is data sourced from interviews, financial reports, SPT Masa, Annual SPT and documentation. Data analysis techniques used include content analysis or content analysis, which is a method of research with certain stages to extract the essence of an idea or information and then draw a conclusion. The relationship between tax planning and the efficiency of the tax burden is by explaining the causal relationship by comparing the tax planning before and after it is implemented or the Effective Tax Rate (ETR). If this tax aggressiveness effort is legally carried out, then PT. Bagus Satria Mandiri will be able to streamline the tax burden for 2019 of Rp. 153.967.125,- or 27.05%, in 2020 Rp. 265,878,625, - or 37.14% and in 2021 Rp. 392,944,625,- or 84.03%. If accumulated for 3 years the amount of efficiency before and after tax aggressiveness with a saving value of Rp. 812,790,375,- or the average percentage is 46.38% per year.